1976
DOI: 10.1002/jez.1401970205
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the shape of the developing vertebrate nervous system analyzed experimentally, mathematically and by computer simulation

Abstract: Two forces are necessary and sufficient to produce the transformation of the newt neural plate from a hemispheric sheet of cells one cell thick to a keyhole shape. These forces are: (1) a regionally programmed shrinkage of the surface of the neural plate (accomplished by contraction of the apical surfaces of the neural plate cells and elongation of these cells perpendicular to the plate); and (2) displacement of the whole sheet caused by elongation of either the notochord or the overlying neural plate cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
167
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(175 citation statements)
references
References 28 publications
7
167
1
Order By: Relevance
“…In the area studied during gastrulation, mitosis orientations were widely distributed, whereas during nerulation mitoses in the subject were quite strongly aligned with the medio-lateral axis. A number of biological studies have suggested that the long axes of cells (Jacobson and Gordon 1976) are key determinants of mitosis orientation (O'Connell and Wang 2000). Other relevant factors may include cell signalling, biochemical factors, mechanical stresses and tissue deformation (Brodland and Veldhuis 2002;Gong et al 2004;Nelson et al 2005).…”
Section: Results and Conclusionmentioning
confidence: 99%
“…In the area studied during gastrulation, mitosis orientations were widely distributed, whereas during nerulation mitoses in the subject were quite strongly aligned with the medio-lateral axis. A number of biological studies have suggested that the long axes of cells (Jacobson and Gordon 1976) are key determinants of mitosis orientation (O'Connell and Wang 2000). Other relevant factors may include cell signalling, biochemical factors, mechanical stresses and tissue deformation (Brodland and Veldhuis 2002;Gong et al 2004;Nelson et al 2005).…”
Section: Results and Conclusionmentioning
confidence: 99%
“…The source of the forces causing these movements in amphibians remained a mystery until explants of tissue actively converged and extended in culture, mechanically isolated from the rest of the embryo (Schechtman 1942;Holtfreter 1944;Jacobson & Gordon 1976;Keller et al 1985). In 900 R. Keller Comparison of the convergence and extension movements in (a) the whole embryo, and (b) an explant of the dorsal sector of the gastrula.…”
Section: Amphibian Convergent Extension Is An Active Force-producingmentioning
confidence: 99%
“…When put in serial opposition with the mesodermal component by barricades at both ends of the extending explant, the neural region buckles in the face of extension of the mesodermal region, arguing that the neural region is the least sti¡ and thus probably weakest extender of the two. In the embryo, the mesodermal tissues are fastened to the overlying neural plate by a strong attachment of the notochord to the region of the neural plate overlying it, the`notoplate' ( Jacobson & Gordon 1976). These attached neural and mesodermal tissues extend together (A. Edlund and R. Keller, unpublished data;Keller et al 1992a).…”
Section: Amphibian Convergent Extension Is An Active Force-producingmentioning
confidence: 99%
“…We also must understand the cellular basis of the convergence and extension movements because of their fundamental role in shaping the nervous system and the early embryo (Jacobson and Gordon, 1976;Schoenwolf, 1985). Although the pattern and underlying cellular mechanisms of convergence and extension of the DIMZ has been investigated extensively (Keller et al, 1985a,b;Wilson et al, 1989;Wilson and Keller, 1991;Shih and Keller, 1992a,b;Keller et al, 1991a,b), we know little about these aspects of the convergence and extension of the DNIMZ (the prospective neural plate).…”
Section: Iymentioning
confidence: 99%
“…A more general significance of these results is that neural induction is best analyzed and understood in terms of the dynamics of the morphogenetic processes involved. INTRODUCTION Convergence (narrowing around the circumference toward the dorsal side of the embryo) and extension (elongation in the anterior-posterior direction) play fundamental roles in both gastrulation (Schechtman, 1942;Keller, 1986;Warga and Kimmel, 1990) and neurulation of vertebrates (Jacobson and Gordon, 1976;Jacobson, 1981;Schoenwolf, 1985;Schoenwolf and Alvarez, 1989). These movements occur autonomously in explants of amphibian embryos and were thought to be region-specific properties of the marginal zone (Spemann, 1938;Schechtman, 1942;reviewed in Keller, 1986;Keller and Winklbauer, 1992).…”
mentioning
confidence: 99%